AN INTEGRATIVE DECISION MAKING MODEL UNDER CRISIS: EXAMINING TWO REAL LIFE CRISIS DECISION MAKING CASES - Zeng, Dechao; Zhang, Xiaoyu (European Scientific Journal, ESJ, 2014)
Researchers have explored extensively into aspects of importance in the decision making process, however, the field of researches on building an integrative decision making model is uncultivated. To bridge the chasm, a systematic decision making model under crisis conditions is built in this paper by integrating factors into the classical decision making model. There are five main elements in the construction of the integrative decision making model, i.e., classical decision making model, decision making under crisis, psychological effects, risk and uncertainty and cross-cultural differences. By incorporating similar elements into integrative factors, three factors as key components in the decision making model, i.e., external environment, risk and idiosyncratic characteristics are listed. The model is expressed in two formats; the first being a simple mathematical formula while the second a flowchart that transforms the abstract thinking process into concrete phases, namely, status quo, identification, development and selection. The focus is centered more on the second method since it matches the reality better. From the analysis, the conclusion is derived that when the decision process is a stochastic dynamic Markov process, the final choice will approach a standard function of the factors in the current state with certain factors dominating the process in different circumstances as the times of making similar decisions increase. In terms of practicability, the model can properly explain the decision processes in the Asiana Airlines crash case and the Jiaduobao Trademark withdrawal case.